(untitled) (Symposium on Natural and Applied Sciences, 2026)
This scientific article provides a deep literary and theoretical analysis of the mechanisms of re-creation of the fate of a creator, in particular an artist, in the genre of the artistic-biographical novel through aesthetic reconstruction. The focus of the research is on the processing of the biography of a real historical figure by artistic thought, the complex relationship between factual accuracy and aesthetic generalization, and the dominance of the author’s consciousness over biographical material. In the novel "The Last Will of Rozi Choriev", the fate of the artist is not presented as a documentary life story, but as a product of artistic-biographical reconstruction, and historical truth is subordinated to the laws of the poetics of the novel. The article examines the ontology of the artistic-biographical novel in comparison with the purely artistic novel, and establishes the aesthetic transformation of the fact in the interpretation of the fate of the creator as an internal necessity of the novel genre. The results of the research show that the artistic-biographical novel is not a depiction of history, but a field for the production of aesthetic meaning, in which the fate of the creator becomes the central expression of the author’s aesthetic concept.